Communism, French patriotism, and Soviet legitimacy in France: social trajectories and nationalism (1945-1954) - Cucchetti, Humberto Horacio (2012)
In the liberation and consolidation context of at that time rising Fourth Republic, communism, having participated in the resistance against the German occupation, played a considerable role in French political life. The Soviet army role during the second world war also allowed the settlement in various spaces of the French society of the time the idea of an intimate solidarity between the people of France and the Soviet Union. Moreover, during the first years of the cold war, the communist networks existing in France, that turned around the French Communist Party, attempted to build legitimacy closely linked to the defense of French patriotism and maintenance, at the level of international relations, of the pro soviets interests. The following contribution proposal attempts to analyze various empirical sources from those years to analyse the specific spaces from which was intended to legitimize the defense of the "Soviet model" in France. To do so, rather than taking as an object the Communist Party itself (often analyzed by French historiography), we propose to approach a vast set of organizational networks that have been commonly known as "transmission belt" of communism in France. Thus, we will enter in a universe of situations and associative frameworks that are deployed for the purpose of our work, from 1945 until 1954. Among others we can mention the Kravchenko affaire (1949), the France-USSR Association, the peace movement and the Action magazine. In all these different areas and situations we will see the deployment of a militancy that, by presenting itself as independent of the partisan organizations, said that the defence of French interests supposed a hard defence of the Soviet model and the sustaining of the Stalinist positions and geopolitical strategies. At the same time, he sought to justify to the public opinion that the critics to this model and to these positions meant to sustain "anti-French" positions. As a result, it could exist a full agreement between French patriotism, nationalism and justification of Communist hegemony in the Soviet Union as in the geopolitical context then under construction. Analysis from the characteristics of such associative networks and specific situations will be completed taking into account also some biographical cases that can illustrate the characteristics of the pro-Soviet legitimating from the individual level. Indeed, the form of vinculation between soviet and nationalism in France meant the construction of a political model that in some biographies meant a (French) nationalist and religious (Catholicism) defence of the Soviet Union in the mid-20th century.